Ring Bersih-G(X) Kuat - Pongoh, Frisca Mareyta (Politeknik Pelayaran Sulawesi Utara, 2023)
Let R be an associative ring with identity, let C(R) denoted the center of R, and let be a polynomial in the polynomial ring C(R)[x]. Ring R is called strongly - clean if every element can be written as with , u is a unit of R, and. The relation between strongly -clean rings and strongly clean rings are determined, some general properties of strongly -clean rings and clean ideal are given. In this paper, by the definition and properties of clean ideal, we introduce definition and properties of-clean ideal with some examples of it. If ring R is -clean we must have that has at least two roots in R. But, for an ideal in ring R, it can be -clean although only has one root in R. The example for this case is given.